Finite element modelling in musculoskeletal biomechanics - Brown, T. D. (Journal of Applied Biomechanics, 2004)
Numerical approximation of the solutions to continuum mechanics boundary value problems, by means of finite element analysis, has proven to be of incalculable benefit to the field of musculoskeletal biomechanics. This article briefly outlines the conceptual basis of finite element analysis and discusses a number of the key technical considerations involved, specifically from the standpoint of effective modeling of musculoskeletal structures. The process of conceiving, developing, validating, parametrically exercising, and interpreting the results of musculoskeletal finite element models is described. Pertinent case study examples are presented from two series of finite element models, one involving total hip implant dislocation and the other involving femoral head osteonecrosis.